1932
DOI: 10.1017/s0021859600054575
|View full text |Cite
|
Sign up to set email alerts
|

The Amounts and Distribution of some Phosphorus and Nitrogen Compounds in wheat During Growth.

Abstract: An account has been given of the lipin, phytin and inorganic phosphorus, and of the protein and non-protein nitrogen present in the wheat plant, from seven weeks before ear emergence until the crop was harvestedThe percentages and amounts of phosphorus and nitrogen so combined, together with their distribution between straw and ear, have been discussed.Relationships between phytin phosphorus and protein nitrogen, and between lipin phosphorus and non-protein nitrogen, have been indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1939
1939
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Previous studies have shown that phytate P constitutes from 49 to 80% of total P of the wheat grain (Knowles and Watkins, 1932;Booth et al, 1941;Asada et al, 1968; Nelson et al, 1968; O'Dell et al, 1972;Abernethy et al, 1973;Bassiri, 1975,1976). In the present study, the ranges for the varieties under dryland were 38-77 and for those under irrigation 73-94%.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that phytate P constitutes from 49 to 80% of total P of the wheat grain (Knowles and Watkins, 1932;Booth et al, 1941;Asada et al, 1968; Nelson et al, 1968; O'Dell et al, 1972;Abernethy et al, 1973;Bassiri, 1975,1976). In the present study, the ranges for the varieties under dryland were 38-77 and for those under irrigation 73-94%.…”
Section: Discussionmentioning
confidence: 99%
“…per acre), and at two stages of growth. Treatment had little effect upon the amount of growth, and the absence of any considerable effects upon the total or inorganicphosphorus contents indicates that little extra phosphorus was taken into the plants .. Knowles and Watkin (1932), using fieid-grown wheat, determined phosphatide, phytin, and "inorganic" phosphorus, firstly, in the total shoots and later in ears and straw separately (9 growth stages in all). Their work is open to criticism in that they air-dried their material, thus giving greater opportunity for hydrolysis and other changes during drying.…”
Section: General Discussion (A) Phosphorus Fractionation In Plantmentioning
confidence: 99%
“…Most of the acid·stable organic phosphorus in endosperm during this period is present as phytic acid (Knowles and Watkin 1922;Harris and Mosher 1934). The relative concentrations of inorganic phosphate and of acid· labile phosphorus decline…”
Section: Whereas Inorganic Phosphorus Previously Increased In Amountmentioning
confidence: 99%